Vodafarms a feasibility study on an alternative livelihood program utilizing soil-less agriculture in wetlands - Azul, Andrew; Francisco, Albert; Go, Reginald; Telosa, Leo (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
The cultivation and sale of vegetables in floating farms have long been used in other water logged countries such as Bangladesh and Myanmar. The implementation of the same system in our wetlands can provide a livelihood for rural communities that are both sustainable and environmentally friendly. Compared to other agricultural practices or other industries utilizing wetlands, soil-less agriculture provides better benefits while reducing costs. Rising poverty and continued land degradation together with poor quality of vegetables are but some of the problems facing the agricultural industry today, soil-less agriculture can provide better yields of organically produced vegetables of high quality but at a cheaper price. Constraints to soil-less agriculture would be wetland and raw material availability. There are numerous possibilities for the implementation of this system in wetlands all over the country that can produce organic vegetables to supply markets at lower prices. At the same time, they provide much needed livelihood for rural communities and promote healthy consumption of vegetables. The study focuses on the introductory implementation of the system on a selected wetland and the cultivation and sale of the vegetables in urban wet markets. An organo-hydroponic agricultural practice in wetlands can provide boundless socio-economic benefits that can help the country in its pursuit of the Millenium Development Goals.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Wetland agriculture; Feasibility studies